An Overview of the Challenges Encountered by Strategic Partners in Implementing Extension Programme: Insights from the Madzivhandila Agricultural of College of Limpopo Province, South Africa - (:unkn) unknown (My University, 2024)
The strategic partnership is an agreed-upon collaboration between businesses with common missions. The purpose of the study is to clarify the roles of strategic partners and the extension and partnerships section at Madzivhandila College of Agriculture. The researcher conducted the study at the College of Agriculture, individual interviews were conducted with the college manager who coordinates the partnership program. In this study, the researchers have adopted a textual analysis to establish the roles of strategic partnerships. It is out of these roles that a broader recommendation, which could be followed by further research to determine their authenticity could be conducted. The findings in this study revealed that there are more than five strategic partners Madzivhandila Agricultural College entered into with; Westfalia, South African Avocado Growers Association (SAAGA), UNIVEG KATOPE, Citrus Growers Association (CGA), Citrus Research International (CRI), Pioneer Hi-Bred RSA (Pty) Ltd, Department of Correctional Services, Perishable Products Export Control Board (PPECB). PANNAR seed, Makhado Specialised Oil Extract enterprise, Ross Breeders Association, Hygro-tech, and SAGA. The challenges that were not addressed in strategic partnerships with colleges need to be addressed urgently for extension work to be effective. The provincial Department of Agriculture and Rural Development should pave the way for the college principals to enter into partnerships with strategic partners and sign MoUs without involving them. The study concludes by suggesting a workable solution as a recommendation between the strategic partners and the college. In conclusion, the researchers discussed how stakeholder analysis was conducted, stakeholder selection, relevant partners, terms of references, and challenges faced by strategic partnerships.
Keywords: African Research